Online Learning Quality Measurement Application for Higher Education: Development and Analysis Using ISO 9126 - Suryanti, Sri; Sutaji, Deni; Nusantara, Toto; ., Subanji (KnE Social Sciences, 2023)
This study aims to develop an application for measuring the quality of online learning in higher education using the analytical hierarchy process (AHP) model and analyze the quality of the application using the ISO 9126 standard. This is a Research and Development study. The application development process uses the software development life cycle (SDLC) method with the waterfall method. Furthermore, the application quality analysis process uses the ISO 9126 standard, consisting of functionality, reliability, efficiency, maintainability, usability, and portability. The results showed that the application for measuring the quality of higher education online learning based on the AHP model had been successfully developed using the SDLC method with the waterfall model. Furthermore, the results of the analysis of application quality using the ISO 9126 standard show that the average results are excellent and suitable for assessing the quality of online learning in higher education. Keywords: online learning, higher education, analytical hierarchy process (AHP), ISO 9126